Reliability and validity of the Chinese version of the instrument of health literacy competencies for health professionals - Huan Qi; Shengguang Chen; Ting Chen; Wei Gan; Dan Yang; Yujie Wang; Qinghua Zhang (Wiley, 2023)
Abstract Aims This study aimed to evaluate the reliability and validity of the Chinese version of an instrument of health literacy competencies for health professionals. Design This study utilized a cross‐sectional design. Methods Authorization was obtained from the authors of the original scale to translate the scale and perform cross‐cultural debugging. From August 2020 to November 2020, 573 health professionals were randomly selected from primary, secondary and tertiary hospitals in Huzhou to examine the reliability and validity of the Chinese version of an instrument of health literacy competencies for health professionals. Results The Chinese version of the scale contains 49 items. The internal consistency Cronbach's α was 0.958 for the total scale and 0.791-0.956 for each dimension. The test-retest reliability was 0.973. Confirmatory factor analysis showed that the fitness degree of the model is good (χ2/df = 1.347, IFI = 0.924, TLI = 0.913, CFI = 0.922, GFI = 0.841, AGFI = 0.815, RMR = 0.011, RMSEA = 0.035). Conclusion The Chinese version of an instrument of health literacy competencies is reliable and valid, which is a credible and effective tool to assess the level of health literacy competencies in Chinese health professionals. Patient or public contribution Health professionals with good health literacy competencies can provide patient‐specific treatment and guidance to promote healthy outcomes for patients.